100 ideas for supporting pupils with dyspraxia and DCD - Kirby, Amanda. 4 0 16; Peters, Lynne; 5 (London : Continuum, 2007)
Shares one hundred ideas for educators to help students with dyspraxia and other learning disabilities, featuring ideas to support students throughout their early, primary, and secondary school years, and including ideas to help develop motor skills, prepare children for independent living, and related topics.
Includes bibliographical references.
Professional.
Keywords: 2 -- 0; 6; Education.;Education. -- Children with disabilities;Movement disorders in children.;Apraxia.;Motor ability in children.;Handicapped children;Movement disorders; 20; 2